Characteristics and risk assessments of mercury pollution in a county region undergoing industrialization in northeastern China: a case study in Gongzhuling - Zhang, Tingting; Hu, Yufei; Wu, Jing; Yin, Shizhong; Huang, Jia; Huang, Wang; Huang, Hongjin; Zhang, Gang (Frontiers in Environmental Science, 2024)
Mercury pollution in emerging industrial zones and surrounding areas, especially in industrial concentration areas, has attracted much attention. So as to clarify the characteristics of Hg in the environment in China’s small and medium-sized industrial emerging and surrounding areas, central urban area of Gongzhuling, a traditional agricultural town with a high degree of industrialization in northeast Changchun industrial base, is taken as the scope. Geological accumulation trin (Igeo) was used to study the degree of soil mercury contamination in Gongzhuling area, latent Er (ecological risk) trin was used to appraise the Er of soil Hg in the study area, and non-carcinogenic risk assessment of mercury in soil using human exposure risk assessment model. The results showed that 34% of soil samples had higher Hg content than the background value of the province’s soil (0.04 mg kg−1). The Igeo results showed that Hg pollution rate of soil in study area was 9% (index >0). In conclusion, the level of soil Hg pollution in Gongzhuling area was low, and the pollution area is mainly concentrated in the northwestern part of the study range. The highest and lowest Er values of soil Hg from the study sample were 2.23 and 214.83, and 24% of the samples had Er > 40, that means they pose a moderate or higher potential ecological risk, and most of these points are located in the northeast of the study range. The main route of human exposure to Hg is oral ingestion. The HQ (non-carcinogenic risk index) and HI (total non-carcinogenic risk value) of soil mercury were both much less than 1, it indicates that the present level of soil Hg in the study range does not pose a threat to local adult health for the time being. This study provides reference for other urban pollution risk assessment, and further defines the direction of future work.